Search for new physics in lepton+photon+X events with 305 pb(-1) of pp collisions at [square root of s] = 1.96 TeV. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We present results of a search for anomalous production of events containing a charged lepton (l, either e or mu) and a photon (gamma), both with high transverse momentum, accompanied by additional signatures X, including missing transverse energy (ET) and additional leptons and photons. We use the same selection criteria as in a previous CDF search but with a substantially larger data set, 305 pb(-1), a pp collision energy of 1.96 TeV, and the CDF II detector. We find 42 lgammaET events versus an expectation of 37.3+/-5.4 events. We observe 31 llgamma+X events versus an expectation of 23.0+/-2.7 events. We find no events similar to the run I eegammagammaET event.